The Similarities and Differences to English Independent Study in the University and Public Libraries: Comparative Study Between Indonesia and Japan - Inayati, Nina; Lestiono, Riski (International Journal of Engineering and Technology, 2019)
This current study was conducted to observe how libraries in Japan and Indonesia are similar and different in regards to supporting English Independent Study (EIS); the investigation was done in both public and university libraries in Chiba and Kyoto (Japan) and Malang (Indonesia). To arrive at the findings, comparative study was conducted by doing site visits to the libraries in Japan and Indonesia; the data collection was done through interview, observation and visitor survey. This study revealed that some indirect supports to EIS activities are detected such as through the availability of physical and digital English collections accessible both online and offline. The similarities found in the investigated libraries covered the unavailability of special English section, the integrated arrangement of English resources along with other resources, challenges in detecting various EIS activities, procurement planning without special attention to English resources, and the same types of collections. The differences of the investigated libraries in both countries were in terms of the arrangement of collections, the procurement of collections, the number of EIS materialsâ€”which was relatively higher for Japanese libraries, and the accessibility of collections. The study was ended by proposing some suggestions for better support of EIS in libraries, such as by considering English based material procurement, establishing special EIS section or giving special tag to EIS collection, and integrating better ICT systems.Â Â